Protocols for Secure Electronic Commerce, Second Edition - Hashem Sherif, Mostafa (CRC Press, 2009)
* Presents a complete compendium of the protocols that secure electronic commerce and online payments * Refers to a companion Web site that contains online presentations on the topics discussed in each section * Assists students and instructors by offering review questions at the end of every chapter * than 250 figures and charts * Provides a solid review of concepts while referring to more detailed or specialized works in the bibliography * Updates the text to reflect technical advances and ongoing developments in emerging areas such as mobile commerce